VALUASI EKONOMI DAN DESAIN LANSKAP KAWASAN WISATA ALAM MANGROVE DI KELURAHAN LAHUNDAPE KOTA KENDARI - Mando, La Ode Agus Salim; Kandari, Aminuddin Mane; Kasim, Safril; Midi, La Ode; Nurgiantoro, Nurgiantoro (MAKILA, 2022)
The mangrove forest, located in the Kelurahan Lahundape in recent years, is being developed as a natural tourism area by the Kendari City Government. The success of its development can be seen in the increasing number of visitors. Thus, this research focuses on assessing the economic valuation of natural tourism services and landscape design of mangrove natural tourism areas. Data collection was carried out in Lahundape Village, West Kendari District, from August to September 2019. The target in this study was divided into 2 (two): 1) human groups and 2) the biogeophysical condition of the mangrove ecosystem. The sample selection on the first target is chosen deliberately, which must meet the sample quota (1152 people). The sample on the second target was obtained from observation and secondary data. Data analysis for the economic valuation of natural tourism uses the travel cost method, including transportation, consumption, parking, tickets, and documentation. The landscape design is determined after analyzing the biogeophysical conditions, facilities, and infrastructure and the motivation and interest of visitors to the Lahundape mangrove natural tourism area. The results showed that 1) the temporary economic valuation of Lahundape Mangrove Natural Tourism was IDR. 491,824,240.-/year. 2) The recommended landscape design is adequate vehicle parking space, worship infrastructure, toilets, connecting roads in mangrove areas, landfills, play infrastructure and docks for boats as attraction facilitation, and the addition of mangrove green lanes.